Clinical Commissioning – what is all the fuss about?. Issue 6 (June 2013) - Watson, Nigel
Clinical commissioning is a broad concept which has many definitions. In its simplest terms it is the process of ensuring clinical services meet the need of the population. It is important that all clinicians have an understanding of commissioning and their role in the process. The aim of this article is explore the need for clinical commissioning and provide a simple explanation of the process and the part clinicians can and will play in changing structures of the NHS.